2019
DOI: 10.3390/su12010030
|View full text |Cite
|
Sign up to set email alerts
|

Residents’ Green Purchasing Intentions in a Developing-Country Context: Integrating PLS-SEM and MGA Methods

Abstract: This paper aims to examine the determinants of green purchasing intentions among different resident groups in a developing-country context. We first expand the theory of planned behaviour (TPB) and build a theoretical model based on green purchasing intention, including attitude, perceived behavioural control, subjective norms, environmental concern, habit, and socio-demographic characteristics (i.e., age, gender, residential area, and educational level). Following this, we collect 552 questionnaires from resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 76 publications
2
39
2
1
Order By: Relevance
“…This was further confirmed by the weak effect size. This is in line with previous studies conducted in Asian contexts [45,57,120]. It is also consistent with some form of common sense, suggesting that consumers' purchasing decisions could easily be influenced by the opinions of, and suggestions from, those who are close to them, such as family and, especially, friends.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This was further confirmed by the weak effect size. This is in line with previous studies conducted in Asian contexts [45,57,120]. It is also consistent with some form of common sense, suggesting that consumers' purchasing decisions could easily be influenced by the opinions of, and suggestions from, those who are close to them, such as family and, especially, friends.…”
Section: Discussionsupporting
confidence: 91%
“…Fourth, the result of this study found strong group aviation in the purchase intention of EEA, consistent with the results of past studies using multi group analysis [47,120]. The combination of PLS SEM and MGA method is very useful because it only examine the behavior but also quantify the variation in the behavior of different groups [134].…”
Section: Theoretical Contributionssupporting
confidence: 90%
See 1 more Smart Citation
“…The relationship between risk perception and perceived behavioral control, and media use and risk perception for people living in rural areas was greater than those living in urban areas. This nding contrasts with a previous study that found people living in the city were more likely to buy green products due to a greater availability of information than those living in rural areas [61]. In the case of COVID-19, people in rural areas may often only use o cial, government media compared to urban residents, who also use social media or WhatsApp groups-where the information may not be valid.…”
Section: Discussioncontrasting
confidence: 78%
“…Presently, there is still no accurate and comprehensive definition to describe GSCM. Different scholars define it in different ways, such as supply chain environmental management (Darnall, Jolley, & Handfield, 2008;Ali, Paksoy, Torgul, & Kaur, 2020), green supply (Yildiz, 2019), green logistics and environmental logistics (Nihan, 2011), green procurement (Wang, 2019), reverse logistics (Hu & Yezi, 2020) or as a series of strategies and methods adopted in the process of SCM (i.e., design, procurement, production and sales) to integrate the concept of environmental protection aimed to sustainable goals. It is also argued that GSCM is a collective capability that combines four different but interrelated sets of practices: environmental management systems, ecological design, resource reduction, and external environmental practices…”
mentioning
confidence: 99%